Pb and Cr content in water, sediment and blood clams (Anadara granosa) from the Panipahan Waters, Pasir Limau KapasSubdistrict, Rokan Hilir Regency, Riau Province - Syahrul Anwar; Sampe Harahap; Budijono Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTHeavy metals in the water might be accumulated in the sediments as well in the benthic organisms such as clam. To understand the Pb and Crcontent, a research has been conducted on May 2019.The water, sediment and clam sampleswere taken from 3 sampling sites, in the area close to mangrove (S1), around the shipyard   and settlement area (S2) and around the port and settlement area (S3). Samplings were conducted 3 times, once / 2 days.Results shown that Pb and Cr content in water  was 0.029 mg/L and 0.007 mg/L, in the sediment was 0.535 mg/kg and 0.204 mg/kg and clam was 0.114 mg/kg and 0.020 mg/kg respectively. The water in all sampling sites can be categorized as polluted, but the heavy metal concentration in the clam obtained from the sampling areas were lower than the safety standard issued by the Indonesian Government, and it might be consumed safely. Keywords:benthic organisms, sediment, bivalve, heavy metal